2010
DOI: 10.1039/c0dt00745e
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-assisted preparation of nanoscale films of thermoelectric PbSe and PbTe and of lead chalcogenide-polymer composite films

Abstract: Polymer films of polyethyleneoxide (PEO) or poly(L-lactide) (PLLA) containing a single-source precursor for either PbSe or PbTe were used to produce films of nanoparticles of these thermoelectric materials. The monomeric homoleptic chalcogenolates lead(II) bis-(2,4,6-trifluoromethylphenylselenolate) Pb[SeC(6)H(2)(CF(3))(3)](2) and lead(II) bis-[tris(trimethylsilyl)silyl-tellurolate] Pb[TeSi(SiMe(3))(3)](2) were used as single-source precursors for the thermolytic formation of the lead chalcogenides. The thickn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Erk et al 179 have produced 30-50 nm PbTe and PbSe particles embedded in polymer films by first spin coating films doped with single precursor (homoleptic chalcogenate) molecules such as lead(II) bis-[tris(trimethylsilyl)silyl-tellurolate] Pb[TeSi(SiMe 3 ) 3 ] 2 in the case of PbTe, which could subsequently be converted by thermolysis to form embedded NCs.…”
Section: Pb Chalcogenidesmentioning
confidence: 99%
“…Erk et al 179 have produced 30-50 nm PbTe and PbSe particles embedded in polymer films by first spin coating films doped with single precursor (homoleptic chalcogenate) molecules such as lead(II) bis-[tris(trimethylsilyl)silyl-tellurolate] Pb[TeSi(SiMe 3 ) 3 ] 2 in the case of PbTe, which could subsequently be converted by thermolysis to form embedded NCs.…”
Section: Pb Chalcogenidesmentioning
confidence: 99%
“…The monomeric homoleptic chalcogenolates lead(II) bis(2,4,6trifluoromethylphenyl-selenolate) Pb[SeC 6 H 2 (CF 3 ) 3 ] 2 and lead(II) bis[tris(trimethylsilyl)silyltellurolate] Pb[TeSi(SiMe 3 ) 3 ] 2 were used as single-source precursors for the thermolytic formation of the lead chalcogenides (PbTe and PbSe) by a spin coating procedure using a polymer-precursor mixture. 93 As the decomposition temperature of the lead chalcogenide precursor is below the degradation temperature of the polymer, nanoparticles of the semiconductor with diameter of 30-50 nm are formed in the polymer layer.…”
Section: Other Single Source Precursorsmentioning
confidence: 99%
“…The key selenol 35 n was prepared through lithiation‐selenylation of 2,4,6‐tris(trifluoromethyl)benzene, followed by treatment with tetrafluoroboric acid (Scheme 41). [93] …”
Section: Synthetic Applications Of Selenolsmentioning
confidence: 99%
“…The key selenol 35 n was prepared through lithiationselenylation of 2,4,6-tris(trifluoromethyl)benzene, followed by treatment with tetrafluoroboric acid (Scheme 41). [93] De Clerck et al reported the synthesis of degradable diselenide-cross-linked nanofibers by aqueous electrospinning of in situ generated selenol-functionalised poly(2-oxazoline)s. The ring-opening reaction of γ-butyroselenolactone with the secondary amine functionalities of partially hydrolysed poly(2-ethyl-2-oxazoline-)-ω-ethylenimine was employed to prepare the key selenol-containing polymers. Interestingly, the morphology and the diameter of such diselenide-crosslinked nanofibers could be controlled by tuning the selenol group content.…”
Section: Synthesis Of Polymers and Metal Complexesmentioning
confidence: 99%